Deficiências minerais em sisal e a “necrose da base das folhas” - de T Alvim, Paulo (Revista Ceres, 1950)
Agave sisalana Perrine was cultivated for 18 months in nutrient solutions of different composition in an attempt to reproduce, under controlled conditions, the disease known as “leaf foot disease”, generally attributed to potassium deficiency. This is the most important sisal disease in Brasil. Hoagland and Arnon’s nutrient solutions were used in the experiment. Alter describing the symptoms of deficiency of phosphorus, potassium, nitrogen, calcium, magnesium, iron, and boron, the author concludes that the “leaf foot disease” does not seem te be caused by potassium deficiency, but by magnesium deficiency. Every symptom of the disease, as occurred in field conditions, had been observed in the plants grown in solutions where no magnesium was available. The fact that the disease may be controlled by potassium fertilization, as reported by some authors, is attributed by the writer to either the presence of magnesium ‘as impurity in the fertilizer used or due to base exchange between potassium and maguesium in the soil.